Propuesta de un proceso de purificación de parafina reciclada, como materia prima en la fabricación de velas industrializadas, que incremente la productividad en la empresa "Velas Lolita's" ubicada en la provincia de Santo Domingo de los Tsáchilas - Pacheco Mena, Remigio Fernando (2022)
The present degree work is focused on improving productivity with a recycled paraffin purification process. The production of candles over time has been industrialized without following improvement parameters such as planning, process distribution, studies of new methods to purify recycled paraffin, etc. The objective of the research is to propose a purification process for recycled paraffin, as a raw material in the manufacture of industrial candles, which increases productivity, for which an individual study of the elements of the problem will be carried out, taking as the main axis the analysis of the costs and productivity of the company, which are immersed and involved in the manufacture of the products. The determination of the current level or state of the process is fundamental in the analysis of the production. Through the analysis and evaluation to purify the recycled paraffin, current process guidelines were obtained and improve the casting stage based on natural methodologies such as decantation, centrifugation where it helps to separate the impurities from the recycled paraffin. Subsequently, the costs of the process improve and it is evidenced with the economic study and the simulation of the Flexsim software that shows performance statistics and feasibility of the proposal. Keywords: paraffin, recycling, process, productivity, costs